Experimental Construction of Full Rolling Fatigue Curve of Couple High-Strength Cast “Iron VCHTG / Steel 18HGT” and its Analysis - L.A. Sosnovskiy (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2014)
Experimental creation of full rolling fatigue curve in the range of durability from N p = 1 (static loading) to 10 8 cycles on the basis of integrated criterion of achievement of a limit state (rapprochement of axes of a specimen and counter specimen δc = δ lim ~ 100 microns) is executed at test of the contact pair high-strength cast-iron ВЧТГ / steel 18XГТ". The basic patterns and obtain the basic characteristics of rolling fatigue resistance. The passport of operability of studied pair is offered and constructed.